2022
DOI: 10.1080/19490976.2022.2073132
|View full text |Cite
|
Sign up to set email alerts
|

Arginine-mediated gut microbiome remodeling promotes host pulmonary immune defense against nontuberculous mycobacterial infection

Abstract: Nontuberculous mycobacterial pulmonary diseases (NTM-PDs) are emerging as global health threats with issues of antibiotic resistance. Accumulating evidence suggests that the gut–lung axis may provide novel candidates for host-directed therapeutics against various infectious diseases. However, little is known about the gut–lung axis in the context of host protective immunity to identify new therapeutics for NTM-PDs. This study was performed to identify gut microbes and metabolites capable of conferring pulmonar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 81 publications
0
21
0
Order By: Relevance
“…Arginine is present in the precursors of various organic compounds such as nitric oxide (NO), ornithine and myosine, which have huge impacts on immune cell biology, especially macrophage, dendritic cell and T cell immunobiology (32,33). Kim et al reported that arginineinduced changes in gut microbiota enhanced host lung immunity to nontuberculous mycobacterial infection, and that indicated that arginine might plays a protective role in lungs (34). Taurine, as conditionally essential amino acid of human, has multiple physiological functions, including the regulation of neural conduction, participating in endocrine activities, immunity enhancement, and strengthening the antioxidant capacity of cytomembrane (35).…”
Section: Discussionmentioning
confidence: 99%
“…Arginine is present in the precursors of various organic compounds such as nitric oxide (NO), ornithine and myosine, which have huge impacts on immune cell biology, especially macrophage, dendritic cell and T cell immunobiology (32,33). Kim et al reported that arginineinduced changes in gut microbiota enhanced host lung immunity to nontuberculous mycobacterial infection, and that indicated that arginine might plays a protective role in lungs (34). Taurine, as conditionally essential amino acid of human, has multiple physiological functions, including the regulation of neural conduction, participating in endocrine activities, immunity enhancement, and strengthening the antioxidant capacity of cytomembrane (35).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several recent studies have suggested a link between inosine and antimicrobial function during bacterial infection. Our recent study showed that inosine, as a metabolite of B. pseudolongum , contributes to antimicrobial responses in mouse models with Mycobacteroides abscessus (Mabc) infection ( Kim et al, 2022 ). Interestingly, ʟ-arginine administration of Mabc-infected mice led to gut microbiota remodeling toward enrichment of B. pseudolongum , which promoted effector T-cell responses with IFN-γ activation and inducible nitric oxide synthase (iNOS) expression, indicating a Th1-mediated M1 shift ( Kim et al, 2022 ).…”
Section: Inosine and Antimicrobial Immunitymentioning
confidence: 99%
“…Our recent study showed that inosine, as a metabolite of B. pseudolongum , contributes to antimicrobial responses in mouse models with Mycobacteroides abscessus (Mabc) infection ( Kim et al, 2022 ). Interestingly, ʟ-arginine administration of Mabc-infected mice led to gut microbiota remodeling toward enrichment of B. pseudolongum , which promoted effector T-cell responses with IFN-γ activation and inducible nitric oxide synthase (iNOS) expression, indicating a Th1-mediated M1 shift ( Kim et al, 2022 ). Importantly, ʟ-arginine administration upregulated the serum level of inosine in mice infected with Mabc, and inosine treatment exhibited a similar protective phenotype as observed in ʟ-arginine-treated conditions in the context of NTM infections ( Sun et al, 2020 ; Kim et al, 2022 ).…”
Section: Inosine and Antimicrobial Immunitymentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Kim et al. integrated metabolomics and transcriptomics profiles of sera from nontuberculous mycobacterial (NTM) disease patients and identified the NTM infection-mediated impact on the host gut microbiome, serum metabolome, and immune defense against NTM infection ( Kim et al., 2022 ). Overlaying the data from other omics studies onto the metabolic landscape is extremely useful to build a quantitative and integrative model of a target biological system.…”
Section: Mainmentioning
confidence: 99%